2007
DOI: 10.1021/es070871+
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Disinfection Byproduct Formation Resulting from Chlorination of Organic−Nitrogen Precursors in Swimming Pools

Abstract: Clinical studies have documented the promotion of respiratory ailments (e.g., asthma) among swimmers, especially in indoor swimming pools. Most studies of this behavior have identified trichloramine (NCl3) as the causative agent for these respiratory ailments; however, the analytical methods employed in these studies were not suited for identification or quantification of other volatile disinfection byproducts (DPBs) that could also contribute to this process. To address this issue, volatile DBP formation resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
2
11

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(178 citation statements)
references
References 29 publications
(45 reference statements)
8
157
2
11
Order By: Relevance
“…This pH dependency was also confirmed by other studies, since NCl 3 is one of the few DBPs where the pH effect on its formation in pool water was previously investigated (Palin, 1950;Schmalz et al, 2011). Other parameters which have been investigated include the chlorine dosing (Cl/N mass ratio) as well as the different N-based compounds found in pool water which can act as NCl 3 precursors (Li and Blatchley III, 2007;Palin, 1950;Schmalz et al, 2011). Each compound was investigated at different pH values to identify its individual effect on NCl 3 formation (Schmalz et al, 2011).…”
Section: Trichloraminesupporting
confidence: 78%
See 2 more Smart Citations
“…This pH dependency was also confirmed by other studies, since NCl 3 is one of the few DBPs where the pH effect on its formation in pool water was previously investigated (Palin, 1950;Schmalz et al, 2011). Other parameters which have been investigated include the chlorine dosing (Cl/N mass ratio) as well as the different N-based compounds found in pool water which can act as NCl 3 precursors (Li and Blatchley III, 2007;Palin, 1950;Schmalz et al, 2011). Each compound was investigated at different pH values to identify its individual effect on NCl 3 formation (Schmalz et al, 2011).…”
Section: Trichloraminesupporting
confidence: 78%
“…The BFA consist of four compounds which may act as precursor for HANs. Histidine has been identified as precursor for dichloracetonitrile where as creatinine was found not to form HANs (Li and Blatchley III, 2007). It is important to note, that HANs are the most toxic DBP group examined in this study , and HAN have also been reported to be the DBP group that contributes the most to the toxicity of chlorinated pool water (Kramer et al, 2009).…”
Section: Effect Of Ph On Thm Han and Haa Formationmentioning
confidence: 70%
See 1 more Smart Citation
“…full scale treatment) the EEO for removal of combined chlorine was 1.0 kWh m Irradiation time to achieve 90 % removal of the monochloramine produced was 6.4 min, which is less than the time needed for photolysis of combined chlorine in pool water. The pool water contains organic chloramines which to some extent represents part of the combined chlorine as measured by the DPD method (Li and Blatchley, 2007). From this one can conclude that some organic chloramines are less sensitive to degradation by UV than monochloramine.…”
Section: Lamp Characterization and Comparison To Full Scale Systemmentioning
confidence: 91%
“…It must be noted that, even when chlorine and chlorinated compounds are used correctly, reactions leading to DBPs formation are inevitable [3]. The DBPs known at present are shown below [21,57,80]:…”
Section: Water Chlorinationmentioning
confidence: 99%